2019
DOI: 10.1186/s13075-018-1783-9
|View full text |Cite
|
Sign up to set email alerts
|

KCa1.1 and Kv1.3 channels regulate the interactions between fibroblast-like synoviocytes and T lymphocytes during rheumatoid arthritis

Abstract: BackgroundFibroblast-like synoviocytes (FLS) and CCR7− effector memory T (TEM) cells are two of the major cell types implicated in the progression of rheumatoid arthritis (RA). In particular, FLS become highly invasive, whereas TEM cells proliferate and secrete proinflammatory cytokines, during RA. FLS and T cells may also interact and influence each other’s phenotypes. Inhibition of the pathogenic phenotypes of both FLS and TEM cells can be accomplished by selectively blocking the predominant potassium channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Our transcriptome analysis demonstrated that pathways were activated in common with arthritis movement of cells, proliferation and both RA and OA. In an in vitro model of RA, Tanner et al (2019) also showed up regulation of Kcnma1 (message and protein) analogous to that observed with our 72 h cytokine treatment. Furthermore, more recent data suggests a correlation between FLS invasiveness and expression of the β-subunit (KCNMB3) in human samples of FLS from RA patients (Petho et al, 2016).…”
Section: The Pathophysiological Validity Of the 72 H Il1β And Tnfα Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…Our transcriptome analysis demonstrated that pathways were activated in common with arthritis movement of cells, proliferation and both RA and OA. In an in vitro model of RA, Tanner et al (2019) also showed up regulation of Kcnma1 (message and protein) analogous to that observed with our 72 h cytokine treatment. Furthermore, more recent data suggests a correlation between FLS invasiveness and expression of the β-subunit (KCNMB3) in human samples of FLS from RA patients (Petho et al, 2016).…”
Section: The Pathophysiological Validity Of the 72 H Il1β And Tnfα Modelsupporting
confidence: 85%
“…Typically, Ca 2+ -activated channels couple with Ca 2+ entry channels such as transient receptor potential (TRP) channels; they are both activated by the Ca 2+ ions that enter and maintain the membrane potential hyperpolarized to "draw in" further Ca 2+ . In FLS, Ca 2+ -activated potassium channels appear to drive invasiveness of synoviocytes and progression of arthritis in both human and rodent RA models (Petho et al, 2016;Tanner et al, 2019), by increasing production of both inflammatory mediators and catabolic enzymes (Hu et al, 2012;Friebel et al, 2014;Tanner et al, 2015). This is a paradoxical effect for a potassium conductance, that would be predicted to hyperpolarize cells and reduce migration, proliferation and activity in general.…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes the calcium-and voltage-dependent potassium channel KCa1.1. This channel has been implicated in rheumatoid arthritis, the regulation of integrins, and myoblast function [114][115][116]. We also found decreases in expression for the genes for striatin (STRN) and calmodulin 2 (CALM2).…”
Section: Calcium Signaling and Inflammation Related Genesmentioning
confidence: 65%
“…To quantify T lymphocytes, inguinal and popliteal lymph nodes were collected from PIA rats after cardiac perfusion and euthanasia and single cell suspensions were prepared using cell strainers (70 µm). Cells were stained with a panel of antibodies as described [ 37 ], in which the cells were washed with flow cytometry buffer before staining with allophycocyanin-conjugated anti-rat CD3 antibodies (Becton Dickinson, 557030), phycoerythrin-cyanine-7-conjugated anti-rat CD4 antibodies (Biolegend, 201516), phycoerythrin-conjugated anti-rat CD8 antibodies (Becton Dickinson, 554857), fluorescein isothiocyanate-conjugated anti-rat CD25 antibodies (Becton Dickinson, 554865), and biotin-conjugated anti-rat CD45RC antibodies (Invitrogen, MA5-17458), followed by Alexa Fluor 405-conjugated streptavidin (Invitrogen, S32351). Cell fluorescence was measured by flow cytometry, as described above.…”
Section: Methodsmentioning
confidence: 99%